SUSUNAN KEPANITIAAN - Panitia (Lomba Karya Tulis Ilmiah, 2021)
Pembina Kegiatan : Wahyu Andy Prastyabudi, S.Kom.,M.Sc. Pembina Panitia : Rifki Dwi Putranto, S.T. Paramaditya Arisamawati, S.T. Ketua Panitia : Firman Adi R. Sekretaris 1 : Siti Aminah Sekretaris 2 : Fitria Rahma W Bendahara : Annisa Ramadhani Divisi Acara Kordinator : Wafa Murtadho K Anggota : Verina Elista M Dinda Aprilia K Ni Ketut Melzia M.Dawud Emerullah Divisi Humas Koordinator : Leonard Julian A. Anggota : Riska Amalia P Andhika Juliawan Divisi PDD Koordinator : Riyo Oktavian P. Anggota : Thomas Adi K. Rian Gunawan